Hidden hate: the resilience of xenophobia - Creighton, Mathew J. (Columbia University Press, 2024)
"Few political topics evoke intolerance like immigration. Antipathy toward immigrants is a force behind populist movements throughout the world, inclusive of Brexit and the presidency of Donald Trump. The impact of xenophobia is obvious, but a coherent picture of the xenophobe as an individual is more elusive. Anti-immigrant sentiment is easily concealed. Understanding the xenophobe is an essential first step to combating this world wide problem. In Hidden Hate, Mathew Creighton provides a novel model for understanding xenophobia as performative through actions that are at times open and other times hidden. Creighton arrived at this model through survey experiments in the UK, US, the Netherlands, Ireland, and Norway. He questions the assumption that surface level patterns of xenophobia reflect social change, and instead contends that political rhetoric, economic crises, and norms surrounding religious tolerance facilitate the movement of previously concealed intolerance into the open. What appears new is not new, rather it is newly revealed"--